Integrated management of post flowering stalk rot of maize caused by Fusarium verticillioides - and RENU GUPTA, M.K. KHOKHAR*, S.S. SHARMA (Indian Phytopathology, 2014)
Five fungicides, five botanicals and three bio-control agents were evaluated against Fusarium verticillioides, first in vitro and then in field to develop effective management strategies for post flowering stalk rot (PFSR) of maize. Systemic fungicides bavistin and tebuconazole (100% and 97.77%) were found most effective in inhibiting the complete mycelial growth of F. verticillioides in vitro. Maximum inhibition of mycelium growth was observed with Trichoderma viride (46.77%) and 0.2% neem seed extract (76.4%). Under field conditions, combination of bavistin + T. viride as seed treatment with susceptible cultivar Surya revealed maximum increase in seed germination (89.4%), population density of T. Viride (23.5 x 104/g soil), reduction in disease severity (83.8% efficacy of disease control) and mortality at 70 DAS (3.9), average disease rating (1.0) and population density of F. verticillioides (3.3 x 104/g soil). In moderate resistant variety, the trend of efficacy of these treatments was similar. The seed treatment with moderately resistant variety (Pratap Makka 3) + bavistin + T. viride showed superior results on plant vigour and yield component of maize. Thus with the help of these strategies we can reduce the losses caused in maize due to PFSR and can grow maize successfully.